A Cross-sectional Analysis of Women's Participation in the Professions - Blitz, Rudolph C.; Ow, Chin Hock (Journal of Political Economy, 1973)
The professions constitute an intellectual elite. Hence, it is of interest how women fare in this elite. This study attempts to explain differences among states of the proportion of women in the professions based on the 1960 census. This is done with demand and supply equations using the following variables: state per capita income, industrial structure, female educational endowment, availability of domestics, and ratio of male to female professional income. All of the variables performed well except the income variable. The poor performance of the latter seems to be due to its aggregative character and necessary statistical manipulations.